L' « inné » et l' « épigénétique » : le dialogue de Kant avec Platon et Aristote - Marques, Ubirajara Rancan de Azevedo (Studia Kantiana, 2023)
This article aims to analyze the dialogue held between Kant and both Plato and Aristotle in his Reflexionen and Vorlesungsnachschriften. This dialogue will be examined from the positions which ascribe Plato and Aristotle the main sources of, respectively, innatism and sensualism. Although he refuses the dogmatic exclusivity of one and the other theories of representation, Kant still admits a form of innatism. Furthermore, he opts by epigenesis, an embryological theory whose bases had been cast by Aristotle. This course will allow us to underscore Kant's debt regarding certain crystallized versions of Plato's and Aristotle's philosophies, such as, for instance, Hissmann's published critique, recommended by Kant himself, of Dutens" work: Recherches sur l"origine des découvertes attribuées aux modernes.